2021
DOI: 10.1038/s41388-021-01978-0
|View full text |Cite
|
Sign up to set email alerts
|

NSUN2-mediated RNA 5-methylcytosine promotes esophageal squamous cell carcinoma progression via LIN28B-dependent GRB2 mRNA stabilization

Abstract: Abstract5-Methylcytosine (m5C) is a posttranscriptional RNA modification participating in many critical bioprocesses, but its functions in human cancer remain unclear. Here, by detecting the transcriptome-wide m5C profiling in esophageal squamous cell carcinoma (ESCC), we showed increased m5C methylation in ESCC tumors due to the overexpressed m5C methyltransferase NSUN2. Aberrant expression of NSUN2 was positively regulated by E2F Transcription Factor 1 (E2F1). High NSUN2 levels predicted poor survival of ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 57 publications
11
92
0
Order By: Relevance
“…A similar association with cancer progression has been also described for NSUN2 overexpression. High expression of NSUN2 was linked to the development of several cancers such as esophageal squamous cell carcinoma (ESCC) [92], gastric cancer [79], and hypopharyngeal squamous cell carcinoma and [93]. Since our results indicated the high mRNA expression level as the most commonly detected alteration of UHRF1 and NSUN2 genes in PRAD patients, the obtained cell cycle-related BPs for the altered group of UHRF1 and NSUN2 strongly favors the findings of previously conducted studies.…”
Section: Discussionsupporting
confidence: 84%
“…A similar association with cancer progression has been also described for NSUN2 overexpression. High expression of NSUN2 was linked to the development of several cancers such as esophageal squamous cell carcinoma (ESCC) [92], gastric cancer [79], and hypopharyngeal squamous cell carcinoma and [93]. Since our results indicated the high mRNA expression level as the most commonly detected alteration of UHRF1 and NSUN2 genes in PRAD patients, the obtained cell cycle-related BPs for the altered group of UHRF1 and NSUN2 strongly favors the findings of previously conducted studies.…”
Section: Discussionsupporting
confidence: 84%
“…Owing to the advance in detection technologies, accumulating research has verified that m5C modification played a key role in the post-transcriptional modification of gene expression, which was closely related to tumor formation, maintenance, and progression ( 10 , 51 , 52 ). As reported, the m5C writer NSUN2 was proven to stabilize the GRB2 mRNA via m5C dependent manner in esophageal cancer ( 53 ). Some studies have validated that m5C modification played an important role in bladder cancer progression via modulating the stabilization of mRNA ( 6 , 12 ).…”
Section: Discussionmentioning
confidence: 63%
“…Li et al showed that NSUN2 coordinates with lin-28B, a novel m 5 C recognition protein, to catalyze the m 5 C modification of GRB2 and stabilize its mRNA expression. High levels of GRB2 promote the activation of the PI3K/AKT and Ras pathways in esophageal squamous cell carcinoma [30]. We demonstrated that NSUN2 inhibited the Ras activation and decreased the p-ErK level in HCC, which led to the increased sensitivity of HCC cells to sorafenib.…”
Section: Discussionmentioning
confidence: 88%